(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Assesment is an inseparable part of an educational program. The aim of this research was to develop peer assessment and self-assessment for evaluating students’ performance in redox reaction laboratory. This study was conducted in one of high school in Bandung with 42 students as its sample. Peer assessment and self-assessment instrument were found to be valid dan reliable. Implementation stage further showed the potency of this instrument as students performance assessment in which peer and self-assessment was highly correlated with expert assesment results.